Designing and implementing an availability stock business model - Roine, Aku (My University, 2019)
This thesis is done as an assignment for ABB, a Swiss-Swedish technology corporation. The purpose of this thesis is to evaluate the business potential of an availability-based business model titled availability stock. The business model originated in Sweden as a performance-related service solution for customer-led demand. This thesis aims at conceptualizing the business model to help other local ABB units assess the potential of the business model, list the requirements needed for the implementation of the model and evaluate the benefits of the business model both from the customers´ and ABB´s viewpoint. The thesis´ data was gathered through interviews to gain deep understanding of the best practices of the availability stock business model. In addition, various documents, both internal and external, were analysed to gain further understanding of the business model. Thematic analysis was used as the method of analysing qualitative data. As the main finding, a matrix was formed to depict the needed requirements for the implementation of the business model. As another finding, the thesis concludes that it remains uncertain whether the business model can be applied as such to different business environments, although the thesis provides general guidelines for the implementation of the business model. As the final finding, this thesis evaluates the multitude of benefits of the business model for customers and ABB itself.

Tämä pro gradu -tutkielma on laadittu toimeksiantona ABB:lle, sveitsiläisruotsalaiselle teknologiakonsernille. Tutkielman tarkoituksena on arvioida saatavuusperusteisen liiketoimintamallin liiketoiminnallista potentiaalia. Liiketoimintamalli sai alkunsa Ruotsissa vastauksena asiakaslähtöiseen kysyntään. Tämä tutkielma pyrkii käsitteellistämään liiketoimintamallin ja auttamaan muiden maiden paikallisia ABB:n liiketoimintayksiköitä arvioimaan liiketoimintamallin potentiaalia, listaamaan vaatimuksia implementoinnille ja määrittämään liiketoimintamallin hyötyjä sekä asiakkaan että ABB:n näkökulmasta. Tutkielman aineisto kerättiin haastattelujen avulla, tarkoituksena saada syvällistä ymmärrystä liiketoimintamalliin liittyvistä parhaista käytännöistä. Lisäksi moninaisia asiakirjoja, sekä sisäisiä että ulkoisia, analysoitiin lisäymmärryksen saavuttamiseksi. Aineisto analysoitiin teemoittelun ja tyypittelyn keinoin. Tutkielman johtopäätöksissä luodaan matriisi kuvaamaan liiketoimintamallin implementoinnin vaatimuksia. Toisena johtopäätöksenä todetaan, että liiketoimintamallin onnistunut implementointi muissa liiketoimintaympäristöissä on epävarmaa, vaikka tutkielma tarjoaa yleisiä suuntaviivoja implementointiin liittyen. Viimeisenä johtopäätöksenä tutkielma arvioi liiketoimintamallin lukuisia hyötyjä sekä asiakkaiden että ABB:n näkökulmasta.
Keywords: business model design, business model implementation, performance-based contracting